Effects of Stevioside on the Expressions of GLUT 1, GLUT 3, and GLUT 4 Proteins in Diabetic Rat Placenta - Katirci, Ertan; Kendirci-Katirci, Remziye; Korgun, Emin Turkay (Planta Medica, 2023)
The placenta provides maternal–fetal nutrient transport. The primary source of energy for fetus development is glucose and maternal–fetal glucose transport occurs through glucose transporters (GLUTs). Stevioside, a component of Stevia rebaudiana Bertoni, is used for medicinal and commercial purposes. We aim to determine the effects of stevioside on GLUT 1, GLUT 3, and GLUT 4 proteins expressions in diabetic rat placentas. The rats are divided into four groups. A single dose of streptozotocin (STZ) is administered to form the diabetic groups. Pregnant rats receive stevioside to form the stevioside and diabetic + stevioside groups. According to immunohistochemistry results, GLUT 1 protein is found in both the labyrinth and junctional zones. GLUT 3 protein is limited in the labyrinth zone. GLUT 4 protein is detected in trophoblast cells. According to Western blotting results, on the 15th and 20th days of pregnancy, there is no difference in the expression of GLUT 1 protein between groups. On the 20th day of pregnancy, the expression of GLUT 3 protein in the diabetic group is statistically higher compared to the control group. On the 15th day and 20th day of pregnancy, the expression of GLUT 4 protein in the diabetic group is statistically lower compared to the control group. Insulin levels in blood samples derived from rat abdominal aorta are determined by the ELISA method. According to the ELISA results, there is no difference in insulin protein concentration between groups. Stevioside treatment reduces GLUT 1 protein expression under diabetic conditions.
Keywords: Stevia rebaudiana Bertoni; Asteraceae; stevioside; glucose transporter proteins; diabetic placenta; rat